2019
DOI: 10.1177/1091581819848722
|View full text |Cite
|
Sign up to set email alerts
|

Repeat-Dose Toxicity Study of a Lyophilized Recombinant Protective Antigen-Based Anthrax Vaccine Adjuvanted With CpG 7909

Abstract: A recombinant protective antigen (rPA) anthrax vaccine candidate (rPA7909) was developed as a next-generation vaccine indicated for postexposure prophylaxis of disease resulting from suspected or confirmed Bacillus anthracis exposure. The lyophilized form of rPA7909-vaccinated candidate contains 75 µg purified rPA, 750 µg aluminum (as Alhydrogel adjuvant), and 250 µg of an immunostimulatory Toll-like receptor 9 agonist oligodeoxynucleotide CpG 7909 in a 0.5 mL phosphate-buffered suspension. General toxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This observation suggests that the nodules were largely resolved between 2 and 5 weeks after the last injection. Similar nodules associated with IM injection of rPA7909 and CPG 7909, consisting of microscopic inflammation of the skeletal muscle and/or subcutis, have been described previously (Savransky et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This observation suggests that the nodules were largely resolved between 2 and 5 weeks after the last injection. Similar nodules associated with IM injection of rPA7909 and CPG 7909, consisting of microscopic inflammation of the skeletal muscle and/or subcutis, have been described previously (Savransky et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Animals were dosed 14 days prior to start of cohabitation (Study Day [SD] 1), on the day of cohabitation (SD 15), and on gestation day (GD) 7. Administration of two doses 2 weeks apart during the premating period was based on a previous study in rats (Savransky et al, 2019). The additional dose on GD 7 was included to ensure high antibody titers and provide exposure to the test article during organogenesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Rats also respond well to CPG 7909 ODN as a vaccine adjuvant component. 6 The study was conducted under Good Laboratory Practices 13 . The housing and animal care practices met current standards of Association for Assessment and Accreditation of Laboratory Animal Care, and current requirements stated in the Guide for the Care and Use of Laboratory Animals 14 and Animal Welfare Act regulations.…”
Section: Experimental Designmentioning
confidence: 99%
“…5 Vaccination of rats with rPA7909, a vaccine candidate based on the recombinant PA protein (rather than the native PA such as that contained in the culture filtrates used to manufacture AVA), which is also adjuvanted with CPG 7909, produced robust immune stimulation with no systemic toxicity. 6 Clinical safety of AV7909 was subsequently demonstrated in several clinical studies, which showed that AV7909 vaccination was not associated with an increase in adverse events as compared to AVA, with the most common events being injection site reactions. 2,7,8 Young animals are considered appropriate models for pediatric assessments.…”
Section: Introductionmentioning
confidence: 99%